COVID‐19, history, and humility. (27th July 2020) - Jones, David S.
Abstract: Amid the current COVID‐19 crisis, everyone has been called upon to offer assistance. What can historians contribute? One obvious approach is to draw on our knowledge of the history of epidemics and proclaim the lessons of history. But does history offer clear lessons? To make their expertise relevant, some historians assert that there are enduring patterns in how societies respond to all epidemics that can inform our experiences today. Others argue that there are informative analogies between specific past epidemics and our present crisis, for instance between COVID‐19 and prior outbreaks of SARS or influenza. Both strategies can be pursued, but each must be done with care. It is certainly possible to map COVID‐19 onto the classic dramatic structure of an epidemic, but we cannot yet know how it will end, a failure of prognostication that constrains the advice we can offer. It is likewise possible to draw on the history of medical therapeutics and public health interventions to identify the risks we face of both underuse and overuse of our remedies, but we cannot yet judge whether our current commitment to heroic social distancing is warranted. While historians can offer insight, we must temper our contributions with humility.